Structural and Biological Properties of Water Soluble Polysaccharides from Lotus Leaves: Effects of Drying Techniques - Wei Li; Ding-Tao Wu; Fen Li; Ren-You Gan; Yi-Chen Hu; Liang Zou (Molecules, 2021)
In the present study, the influence of five drying techniques on the structural and biological properties of polysaccharides from lotus leaves (LLPs) was investigated. Results revealed that the yields, contents of basic chemical components, molecular weights, and molar ratios of compositional monosaccharides of LLPs varied by different drying technologies. Low molecular weight distributions were observed in polysaccharides obtained from lotus leaves by hot air drying (LLP-H), microwave drying (LLP-M), and radio frequency drying (LLP-RF), respectively. The high contents of bound polyphenolics were measured in LLP-H and LLP-M, as well as polysaccharides obtained from lotus leaves by vacuum drying (LLP-V). Furthermore, both Fourier transform infrared (FT-IR) and nuclear magnetic resonance (NMR) spectra of LLPs were similar, indicating that drying technologies did not change their basic chemical structures. Besides, all LLPs exhibited obvious biological properties, including in vitro antioxidant capacities, antiglycation activities, and inhibitory effects on α-glucosidase. Indeed, LLP-H exhibited higher 2,2-azidobisphenol (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging ability (IC50 values, LLP-H, 0.176 ± 0.004 mg/mL; vitamin C, 0.043 ± 0.002 mg/mL) and 2,2-diphenyl-1-(2,4,6-trinitrate phenyl) hydrazine radical scavenging ability (IC50 values, LLP-H, 0.241 ± 0.007 mg/mL; butylated hydroxytoluene, 0.366 ± 0.010 mg/mL) than others, and LLP-M exerted stronger antiglycation (IC50 values, LLP-M, 1.023 ± 0.053 mg/mL; aminoguanidine, 1.744 ± 0.080 mg/mL) and inhibitory effects on α-glucosidase (IC50 values, LLP-M, 1.90 ± 0.02 μg/mL; acarbose, 724.98 ± 16.93 μg/mL) than others. These findings indicate that both hot air drying and microwave drying can be potential drying techniques for the pre-processing of lotus leaves for industrial applications.